PERSEPSI DOSEN IAIN TAKENGON TERHADAP KUALITAS PEMBELAJARAN MAHASISWA DALAM MASA COVID-19 - Musradinur Musradinur; Delfia Herwanis (PIONIR: JURNAL PENDIDIKAN, 2021)
All sectors of human life are currently faced with the spread of Covid-19, and it also has an impact on the world of education. Universities at this time cannot carry out the teaching and learning process as usual face-to-face, but must carry out distance lectures or what is also known as online learning. This study aims to determine the perceptions of lecturers at the Takengon State Islamic Institute of the quality of student learning during the Covid-19 period, so that it can be an evaluation for lecturers and students in carrying out the teaching and learning process in the future when carrying out the learning process, so this research becomes a reference on which side. This study used a qualitative approach with a survey method by sending a questionnaire instrument via googleform to lecturers in the Takengon State Islamic Institute, then analyzed using descriptive techniques to analyze qualitative data. It can be concluded that in general, from the 12 question items that have been asked, there are various opinions given by respondents. The results obtained as a whole indicate that the lecturers' satisfaction with students is sufficient. However, whatever the results are now, this is a picture of the services that have been provided, and God willing, in the future there will be an improvement and progress to build the best service, especially at IAIN Takengon.